The Relationship Between Gratitude and Body Image for Students of Management Study Program, University of Muhammadiyah Sidoarjo - Fifi Ismi Sari; Eko Hardi Ansyah (Journal of Islamic and Muhammadiyah Studies, 2022)
Students who are not satisfied with their body shape will evaluate their body image, namely the perception of what they believe and feel about their body shape. Students who accept their appearance will always keep what they have. The purpose of this study was to determine The Relationship between Gratitude and Body Image of Management Study Students At The University of Muhammadiyah Sidoarjo. This research is a type of quantitative research with a correlational approach. The population in this study were students of the management study program at the University of Muhamadiyah Sidoarjo, amounting to 873 female students. The sample in this study was 247 female students with stratified random sampling technique. Data collection techniques in this study used a gratitude scale (ɑ = 0.751) and a body image scale (ɑ = 0.870). The data analysis technique used Spearman's correlation with the help of SPSS 22.0. The results of the data analysis of this study indicate that the correlation coefficient (rxy) is -0.015 with a significance of 0.811 > 0.05, which means that there is no significant relationship between gratitude and body image in management study students at the University of Muhamadiyah Sidoarjo.